Deep Learning for Personalized Medicine - Enhancing Precision Health With AI - Raparthi, Mohan; Prasad Kasaraneni, Bhavani; Reddy Gayam, Swaroop; Kanth Kondapaka, Krishna; Pushyamitra Pattyam, Sandeep; Putha, Sudharshan; Kumar Sahu, Mohit; Sarana Kuna, Siva; Siva Prakash Nimmagadda, Venkata; Thuniki, Praveen (Journal of Science & Technology, 2020)
Personalized medicine, a paradigm that tailors medical treatment to individual characteristics, is revolutionizing healthcare. One of the key enablers of this revolution is deep learning, a subset of artificial intelligence (AI) that excels at extracting patterns from complex data. This paper explores the role of deep learning in personalized medicine, focusing on its contributions to enhancing precision health initiatives through tailored treatment and diagnosis. We discuss how deep learning algorithms analyze diverse datasets, including genomics, imaging, and clinical records, to generate insights that guide personalized interventions. We also examine the challenges and ethical considerations associated with implementing deep learning in personalized medicine. Through this investigation, we highlight the transformative potential of deep learning in advancing precision health and improving patient outcomes.
Keywords: Deep Learning; Personalized Medicine; Precision Health; Artificial Intelligence; Healthcare; Genomics; Imaging; Clinical Records; Tailored Treatment; Diagnosis